Enhancement of the anticoagulant capacity of polyvinyl chloride tubing for cardiopulmonary bypass circuit using aluminum oxide nanoscale coating applied through atomic layer deposition. Issue 3 (7th September 2021) - Wang, Chen‐Chie; Wang, Li‐Chun; Yang, Kai‐Chiang; Chen, Miin‐Jang; Lin, Hsin‐Chih; Han, Yin‐Yi
Abstract: For cardiopulmonary bypass, the polyvinyl chloride (PVC) circuit which can initiate the activation of platelets and the coagulation cascade after blood cell contacting is the possible detrimental effect. Surface coating of the PVC tubing system can be an effective approach to enhance circuit's hemocompatibility. In this study, aluminum oxide (Al2 O3 ) thin films were deposited through thermal atomic layer deposition (T‐ALD) or plasma‐enhanced ALD (PE‐ALD) on PVC samples, and the anticoagulation of the Al2 O3 ‐coated PVC samples was demonstrated. The results revealed that Al2 O3 deposition through ALD increased surface roughness, whereas T‐ALD had a relative hydrophilicity compared with blank PVC and PE‐ALD. Whole blood immersion tests showed that blood clots formed on blank PVC and that a large amount of red blood cells was found on PE‐ALD substrates, whereas less blood cells were noted in T‐ALD samples. Both T‐ALD and PE‐ALD Al2 O3 films did not cause activation of blood cells, as evidenced in CD3 + /CD4 + /CD8 +, CD61 + /CD62P +, and CD45 + /CD42b + populations. Analysis of serum coagulation factors showed that a lower amount of prothrombin was absorbed on T‐ALD Al2 O3 samples than that on blank PVC. For albumin and fibrinogen immersion tests, immunostaining and scanning electron microscopy further revealed that a thin albumin layer was absorbed on T‐ALD Al2 O3 substrates but not on PVC samples. This study revealed that deposition of Al2 O3 films by T‐ALD can improve anticoagulation of the PVC tubing system.